Nigeria and West Africa: Fodder banks. Dry-season feed supplementation for traditionally managed cattle in the subhumid zone - Mohamed-Saleem, M.A.; Suleiman, H. (1986)
Presents results of trials conducted by ILCAs' subhumid zone team on dry-season feed supplementation for traditionally managed cattle in the subhumid zone of West Africa. Discusses fodder bank development for pastoralists, constraints to fodder bank development, pastoralists' adoption and perception of fodder banks, and long term prospects for fodder banks. Includes data on yield and quality of a stylosantes g. fodder bank, effect of different land preparation and seed treatment methods on stand count of stylo, and yield & stylo composition of fodder banks.